Relationship between prostate cancer and atypical small acinar proliferation (Annals of Medical Research, 2021)
Aim: To investigate the prostatic adenocarcinoma (PA) detection rate in follow up biopsies with an initial diagnosis of atypical small acinar proliferation (ASAP).Materials and Methods: In this study, the cases of ASAP diagnosis in prostate needle biopsy materials between January 2010 and December 2016 were retrospectively analyzed and the correlation between the results and the follow-up diagnoses of ASAP-diagnosed cases was investigated.Results: 62 cases with ASAP were included in the study and 21 (34%) of them were detected as PA after the follow-up diagnoses. Also ASAP and PA were detected at different localizations in 38% of the cases.Conclusion: We are on the opinion that it is important to increase the number of samples taken from other localizations as well as ASAP diagnosed quadrants when taking follow-up biopsies.
Keywords: Atypical Small Acinar Proliferation; Prostate Cancer; Prostate Needle Biopsy